2013
DOI: 10.1007/s10551-013-1901-1
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and the Climate Change Issue: An Exploratory Study of Cluster and Extra-Cluster Effects

Abstract: Climate change, while potentially impacting many industries, appears to have considerable significance to the wine industry. Yet little is known about how firms acquire knowledge and gain an understanding of climate change and its impacts. This study, exploratory in nature and studying firms from the wine-producing region of Tasmania, is one of the first in the management literature to use cluster theory to examine the climate change issue. Firms are predicted to exchange knowledge about climate change more re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…It may also result in advantages of common ownership, incentives, and innovation, as well as economies of scale and other cost reductions. Maskell remarked on this point, "most of the advantages in relation to the skills developed in the local market might be just as big or small for 20 co-localized firms of a given size as for a single firm, 20 times bigger" (Maskell, 2001, p. 97; similar comments are made by Galbreath et al, 2014).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…It may also result in advantages of common ownership, incentives, and innovation, as well as economies of scale and other cost reductions. Maskell remarked on this point, "most of the advantages in relation to the skills developed in the local market might be just as big or small for 20 co-localized firms of a given size as for a single firm, 20 times bigger" (Maskell, 2001, p. 97; similar comments are made by Galbreath et al, 2014).…”
Section: Introductionmentioning
confidence: 91%
“…The cluster could evolve a selective/adoptive/innovative mechanism that creates the common training system by a process of selection, imitation, variation, and monitoring of identified solutions (Maskell, 2001, p. 930;Galbreath et al, 2014). At the same time, this process cannot abandon an individual perspective: the training offer must be aligned with the self-defined objectives of each enterprise, facilitated or delimited as this may be by a specific institutional endowment.…”
Section: What Is the Nature Of The Interfirm Training Cluster?mentioning
confidence: 99%
“…To reduce vulnerability to climate change, knowledge and innovation are crucial for identifying novel ways of production and implementing change (Galbreath et al, 2014). Innovation has long been essential to generating new ideas and technologies (March, 1991).…”
Section: Research and Development Spendmentioning
confidence: 99%
“…To reduce vulnerability to climate change, knowledge and innovation are crucial for identifying novel ways of production and implementing change (Galbreath et al , 2014). Knowledge drives innovation to address problems that require diverse perspectives, such as decoupling greenhouse gas emissions and industrial-scale agricultural industries, and managing the change required for adopting new practices (Ward et al , 2016).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Competition and collaboration amongst firms are even crucial in promoting an understanding of climate change and its aftermaths. Analysing cluster and extra-cluster effects within the wine industry, Galbreath et al (2014) found that firms acquire knowledge around climate issues both from a variety of exchanges with other firms and from other knowledge sources.…”
Section: Actors Involved and Their Motivationsmentioning
confidence: 99%